Joints with lockbolts in steel structures – Part 1: Lockbolt technology. Issue 2 (15th May 2020) - Glienke, Ralf; Schwarz, Mathias; Ebert, Andreas; Blunk, Christoph; Wanner, Martin‐Christoph
Abstract: Many mechanical joints in steel structures use conventional bolts. Nevertheless, this proven jointing technology has some significant disadvantages. These basically include the high levels of scatter during application of the assembly preload using the torque‐controlled tightening process, the risk of loosening during cyclic loads due to transverse displacement of the components and the low fatigue resistance under axial loading. Lockbolt technology was invented as long ago as the 1930s and mainly used for the aviation and space industry because of its evident advantages. This jointing technology has been constantly further developed in response to the most diverse demands from sectors such as aviation, commercial vehicles, rail vehicles, agricultural machinery, defence technology and steel structures. The application of lockbolt technology, which is primarily used in mechanical engineering, was in most cases based on individual studies, since no consistent rules and guidelines were available for the design and execution of lockbolt connections in steel structures. Within the scope of several public research projects funded by the AiF (German Federation of Industrial Research Associations) and conducted by the iGF (Industrial Collective Research) organization as well as through approval investigations, the Fraunhofer Institute for Large Structures in Production Engineering (IGP) has successively developed the necessary design rules according to the EN 1993 standard (Eurocode 3) for use in structural connections. This paper presents connections with lockbolts in steel structures. Following an introduction to lockbolt technology and the assembly preload of lockbolts, the securing effect and corrosion protection of lockbolts are presented.